ANALISIS FAKTOR-FAKTOR PELATIHAN TENTANG KEWIRAUSAHAAN KEPADA PELAKU USAHA MIKRO KECIL MENENGAH DI PUSAT LAYANAN USAHA TERPADU KOPERASI USAHA MIKRO KECIL MENENGAH KABUPATEN CIANJUR - Dandi Bahtiar; Gita Rianti (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2021)
The purpose of this research is to examine the quality of human resources of the trainers at the Center for Integrated Business Services of the Cooperative, Micro, Small and Medium Enterprises, Cianjur Regency (PLUT-KUMKM). The questionnaire was conducted for Micro, Small and Medium Enterprises (UMKM) actors who had conducted training at PLUT-KUMKM Cianjur. The number of registered trainees is 300 people. The number of samples using the Slovin formula was result 100 people. The sampling method uses probability sampling techniques, simple random sampling, which is a random sampling technique without paying attention to strata (Sugiyono, 2017). The data analysis used was descriptive analysis, namely the analysis to describe the quality of the trainers. The second analysis is factor analysis with the aim of identifying groups between variables (Aldy Purnomo, 2016), so that variables have a high appearance are found. The results of the Kaiser-Meyer Olkin (KMO) are 0.680 and the value of the Measure of Sampling Adequacy (MSA) of all variables is more than 0.50. That is implies that observation by factor analysis is more than sufficient and reliable. The results showed that the average respondent's response to the training variable was 4.25 is means very good. From this research formed 4 factors, 3 new factor that emerged is "Ability, Skills and Understanding of Participants"; "Motivation of Participants"; and "Competencies of Instructor". Then the other factor is "Method" remains appropriate because it has a strong correlation. The 4 factors is able to explain all research variables as much as 54.3%.